Trade Liberalisation, Economic Growth and Human Resource Development in Nigeria: Causal Implications (1980-2009) - Gabriel, Aremo Adeleke (Journal of Economics and Behavioral Studies, 2013)
The study examined the causal links among trade liberalisation, economic growth and human resource development in Nigeria with a view to identifying the nexus connecting these three variables. Inferences of causality were drawn within the framework of Vector Auto-regression model employing techniques of analysis involving unit root test, cointegration and Granger causality tests. The findings that emerged from the analysis show that economic growth granger-caused both poverty level and trade liberalization in Nigeria. Besides, trade liberalization equally predicted poverty level. The study therefore concluded that it is desirable for government to initiate strategies that would further boost economic growth in Nigeria in order to alleviate poverty and to derive maximum benefits from trade liberalization. In addition, government should further diversify the productive base of the economy, and ensure proper integration of the key sectors of the economy to enhance output growth. In order to reduce poverty level, trade liberalization needs to be further embraced using multi-dimensional approaches such as more tariff reduction, and systematic reduction or removal of other forms of quantitative and qualitative restrictions on goods and services.